A single-center investigation on serotypes, drug resistance and clinical significance of GBS isolates from pregnant and non-pregnant adults in Baoji, China - Chen, Siyu; Li, Haiying; Guo, Mengyang; Wang, Hua; Gao, Wei; Cui, Yating; Zhang, Yani; Yuan, Lin; Shi, Wei; Yao, Kaihu (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesTo assess the epidemiology, serotype distribution, and antimicrobial resistance of GBS among both pregnant and non-pregnant adults in Baoji, China, addressing an existing gap in current research.MethodsBased on the GBS strains identified in the clinical laboratory from 2016 to 2024, information on age, gender, specimen type, and diagnosis was collected for the corresponding adult cases, including both colonization and infection cases. GBS was identified using three methods: mass spectrometry, CAMP test and latex agglutination kit for streptococcal serotyping. Serotypes were determined by latex agglutination, and antimicrobial susceptibility was tested against 20 antimicrobials using an automated drug susceptibility system.ResultsA total of 200 GBS strains were collected, in which 107 were from pregnant women, and 93 from non-pregnant adults including 34 males. Clinical pathogenic isolates were defined for 86 cases, in which the urinary tract infections were predominant (61.6%), and invasive infections were confirmed for 16 cases (18.6%). A total of 5 serotypes were identified in the present 200 strains, including serotype Ib (34.5%), V (26.0%), III (21.5%), Ia (2.0%) and VIII (1.0%). In addition, 30 strains (15.0%) were non-typeable (NT). The coverage rate of the hexavalent vaccine currently in development is 84.5%. Significant differences are observed in the proportions of serotypes Ib, III, and/or V across various age groups, pregnancy statuses, and between colonized and infectious strains. Notably, the proportion of serotype V varies markedly, with 32.3% in the 18–39 age group versus 18.9% in the 40–64 age group and 10% in the >64 age group, 36.4% in pregnant women compared to 14.0% in non-pregnant women, and 34.2% in colonized strains as opposed to 15.1% in infectious ones. All 200 GBS strains were sensitive to penicillin, and the resistance rates to erythromycin, azithromycin, levofloxacin, clindamycin, tetracycline, and chloramphenicol were 93.5%, 93.5%, 70.5%, 70.0%, 53.5%, and 13.0%, respectively.ConclusionThe present findings suggest that GBS may potentially infect and colonize adults, regardless of gender or age, in Baoji, China. Serotypes Ib, III, and V are common serotypes, but their frequency is related to the host’s age group, pregnancy status, and clinical relevance. GBS isolates are still generally susceptible to penicillin.